2010
DOI: 10.1111/j.1467-629x.2010.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the structure of audit workpaper error knowledge and its relationship with workpaper review performance

Abstract: This study examines the veracity of two important, yet untested, premises underlying the interpretation of hierarchical variation in workpaper review performance. Prior research has argued that auditors at different hierarchical levels structure their knowledge of workpaper errors differently, and that these differences in knowledge structure give rise to hierarchical variation in the ability of auditors to identify mechanical and conceptual workpaper errors. This study directly examines the way in which audit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…It is widely reported that individuals rely on their knowledge and experiences to interpret the environmental stimuli they encounter in their decision making process (Harding, 2010). In a review of the literature, Maheswaran and Pinder (2010) conclude that experience and education are the two important elements that substantially affect Audit expectation gap the quality of decisions of finance managers.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely reported that individuals rely on their knowledge and experiences to interpret the environmental stimuli they encounter in their decision making process (Harding, 2010). In a review of the literature, Maheswaran and Pinder (2010) conclude that experience and education are the two important elements that substantially affect Audit expectation gap the quality of decisions of finance managers.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Individual factors, such as knowledge and experience, shape human judgment and attitude (Bolisani and Scarso, 1999), and influence human decision making (Collan and Lainema, 2005; Epstein and Geiger, 1994; Humphrey et al , 1992; Mansori, 2012). It is widely reported that individuals rely on their knowledge and experiences to interpret the environmental stimuli they encounter in their decision making process (Harding, 2010). In a review of the literature, Maheswaran and Pinder (2010) conclude that experience and education are the two important elements that substantially affect the quality of decisions of finance managers.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Standards also require that all audit documentation be reviewed by at least one other audit team member (PCAOB 2016, AS 1201. The initial creation of audit documentation (Payne and Ramsay, 2008;Shankar and Tan, 2006;Andiola et al, 2018), as well as the review process (Fargher et al, 2005;Lambert and Agoglia, 2011;Brazel et al 2004;Frank and Hoffman, 2015;Agoglia et al 2010;Hun-Tong Tan and Trotman, 2003;Rosman et al, 2007;Payne et al, 2010;Harding, 2010;Bamber and Ramsay, 2000), are critical in meeting audit standards and completing a quality audit. In the case of failed audits, the finalized audit documentation is the key evidence in auditor negligence trials (Backof, 2015).…”
Section: The Accounting Review Processmentioning
confidence: 99%
“…Probably, the nature of the allowance for doubtful accounts has led scholars to address this topic in several studies. In addition to early studies on the estimation method (Cyert et al, 1962;Schroderheim, 1964;Van Kuelen et al, 1981;Grimshaw and Alexander, 2011), the allowance for doubtful accounts has also been taken into consideration when examining a number of issues, such as the audit workpaper review process (Harding, 2010;Reimers and Fennema, 1999;Shankar and Tan, 2006), the effects of audit partner rotation among US publicly listed firms (Laurion et al, 2017), the responsiveness of audit program plans to client risks (Mock and Wright, 1999) and the effects of fraud risk assessments on auditors' evaluation of evidence and judgment (Rose and Rose, 2003). Furthermore, the allowance for doubtful accounts has been used in case studies for auditing courses at undergraduate and graduate levels (Andiola et al, 2018).…”
Section: Research Question and Backgroundmentioning
confidence: 99%